Multi‐family therapy for separated parents in conflict and their children: intervention development and pilot evaluation. Issue 1 (22nd November 2021) - Mortimer, Rose; Morris, Emma; Pursch, Benita; Roe, Alice; Sleed, Michelle
Abstract: Evidence demonstrates the deleterious impact of ongoing and poorly resolved parental conflict on children's wellbeing. 'No Kids in the Middle' (NKM) is a multi‐family programme that aims to help high‐conflict separated parents find new ways of communicating. The aim of this study was to adapt, deliver and evaluate NKM in three UK pilot sites. This paper reports findings from interviews exploring families' experiences of this intervention, and questionnaires which measured change for families over the course of the programme. Parents reported reductions in hostility and conflict when discussing parenting issues. Children reported improved wellbeing with respect to family life, and a reduction in 'avoidance' with respect to talking or thinking about parental conflict. Parents reported reduced internalising symptoms in children. The findings indicate that NKM could be a promising intervention for high‐conflict separated parents and their children, deliverable by frontline practitioners. Practitioner points Inter‐parental conflict can negatively impact children's wellbeing Multi‐family therapy may be a promising approach for separated parents experiencing co‐parenting conflict After the NKM multi‐family programme, parents reported reduced levels of hostility and conflict when discussing parenting issues At the end of the NKM programme, children reported improved wellbeing with respect to family life, and a reduction in 'avoidance' with respect to talking or thinking about family conflict. Relatedly, parents reported reduced internalising symptoms in children